Criminological Juridical Analaysis of The Crime of Premeditated Murder of a Beautiful Model in Pandeglang District - Dewi Fadhia Gayatri gayatri; Hasuri (Warmadewa Press, 2024)
This research aims to find out what factors make the perpetrators of murder commit these acts seen from the theory of criminology. In this research the author uses the Empirical Normative Legal Research methodology. This empirical normative legal research method is basically a combination of normative legal approaches by adding various empirical elements. To collect data in this study, researchers used secondary data, namely data obtained from literature. The usefulness of secondary data is to find initial data or information, obtain a theoretical basis or legal basis, obtain limitations, definitions, meaning of a term. Judging from the theory of criminology, the perpetrators of the crime of murder are motivated by two factors, namely revenge factors (heartache) and social environmental factors. The perpetrator is subject to Article 340 of the Criminal Code